2008
DOI: 10.1128/aem.00801-08
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Biofilm Continuous Culture Method for Simultaneous Assessment of Architecture and Gaseous Metabolite Production

Abstract: The way that gaseous metabolite production changes along with biofilm architecture development is poorly understood. To address this question, we developed a novel flow reactor biofilm culture method that allows for simultaneous assessment of gaseous metabolite production and architecture visualization. In this report, we establish the utility of this method using denitrification by Pseudomonas aeruginosa biofilms as a model system. Using this method, we were able to collect and analyze gaseous metabolites pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Biofilm formation reached a peak at 12 h in this flask. When the P. aeruginosa biofilm incubated for 12 h was observed by a confocal reflection microscopy technique, as described previously, 12) the presence of 1 and 2% ethanol resulted in increased biofilm formation at a thickness greater than 20 μm, though it was less than 10 μm in the absence of ethanol ( Fig. 1(B)).…”
Section: 2)mentioning
confidence: 99%
“…Biofilm formation reached a peak at 12 h in this flask. When the P. aeruginosa biofilm incubated for 12 h was observed by a confocal reflection microscopy technique, as described previously, 12) the presence of 1 and 2% ethanol resulted in increased biofilm formation at a thickness greater than 20 μm, though it was less than 10 μm in the absence of ethanol ( Fig. 1(B)).…”
Section: 2)mentioning
confidence: 99%
“…However, when visualizing substrate penetration into biofilms solely with FCLSM, it is necessary to label the entire biofilm with another fluorescent dye or fluorescent proteins. In contrast, CRM enables the visualization of three-dimensional samples without fixation and fluorescent labeling (14,15,20). Thus, CRFP uses a simple procedure to track the penetration of fluorescent compounds while visualizing the entire structure of biofilms.…”
mentioning
confidence: 99%
“…3). In a previous study, we reported that P. aeruginosa forms a three-dimensional mesh-like structure also under denitrifying conditions (20). SYTO9 fluorescent dye was added to the P. aeruginosa biofilm, and confocal images were acquired with both CRM and FCLSM at 1-min intervals after adding the dye.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Natural samples such as activated sludge were observed with this technique as were model organisms, resulting in a high resolution that is comparable to the utilization of fluorescent proteins and dyes (170,171). By combining this technique with other techniques, it is possible to measure gas metabolites under anaerobic conditions and observe the correlation of the biofilm structure and material diffusion in biofilms (170,172).…”
Section: Life Is Not As Simple As It Seemsmentioning
confidence: 99%